Specific Targeting of Notch Ligand-Receptor Interactions to Modulate Immune Responses: A Review of Clinical and Preclinical Findings - Goruganthu, Mounika U. L.; Shanker, Anil; Dikov, Mikhail M.; Carbone, David P. (Frontiers in Immunology, 2020)
Understanding Notch signaling and targeting it effectively has long been valued in the field of immunology and cancer. Here, we discuss prominent discoveries at the intersection of Notch signaling, cancer and immunology. While there is a plethora of Notch inhibitors and Notch-based therapeutics tested both in vitro and in clinic, undesirable off-target effects and therapy-related toxicities have been significant obstacles. We make a case for the clinical application of Notch ligand-based moieties as immunomodulatory agents and discuss major research findings with an emphasis on enhancement of antigen-specific adoptive T cell responses and generation of long-lived effector memory T cells using preclinical models of lung cancer.